The Polar Amplification Model Intercomparison Project PAMIP – Emerging Results and Lessons Learned - Semmler, Tido; Jung, Thomas; Streffing, Jan (Zenodo, 2020)
This is a summary of emerging results from the Polar Amplification Model Intercomparison Project, a project under the umbrella of CMIP6, the Coupled Model Intercomparison Project. The focus is on the influence of Arctic sea ice loss on the Northern mid-latitude climate.